Pembelajaran Teks Cerita Fantasi Melalui Struktur dan Unsur pada Mata Pelajaran Bahasa Indonesia Kelas VII SMP Negeri 1 Tambakboyo - Sukmariantika, Alldila Zuneasili; Setiawan, Arif; Prihatini, Arti (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This study aims to (1) describe the learning of fantasy story texts for class VII students of SMP Negeri 1 Tambakboyo, (2) describe the learning outcomes of students of SMP Negeri 1 Tambakboyo through the structure and elements of fantasy story texts. This type of research is descriptive qualitative with case study method. The source of the data in this study was fantasy story text written by Indonesian language students and teachers in class VII-F and VII-G of SMP Negeri 1 Tambakboyo. Data collection carried out in this study, namely direct observation, interviews, and data analysis. The results of the research show the following things. First, Tambakboyo 1 Public Middle School students are able to understand fantasy story text material through an integrative learning model. Second, Tambakboyo 1 Public Middle School students are able to understand the structure of fantasy story texts well, namely by mentioning the orientation, complications, and resolution in their writing. Third, in their writing the Tambakboyo 1 Public Middle School students have fulfilled the elements of fantasy story text based on expert opinion, namely by mentioning the theme, plot, characters and characterizations, setting, point of view, and message.